Yoga Asana dalam Pengelolaan Diabetes Melitus Tipe 2: Implikasi Klinis dan Peran Dokter dalam Konteks Wisata Kesehatan - Ni Nyoman Ayu Trisna Anggarini; Made Kurnia Widiastuti Giri; Nyoman Ratih Widya Sari; Kadek Listia Prasetya Dewi; Dewa Ayu Aryantika Anggraeni; Ni Putu Ayu Daneswari Dewi (Pusat riset dan Inovasi Nasional, 2026)
Type 2 diabetes mellitus (T2DM) requires comprehensive management beyond pharmacological therapy, including sustainable lifestyle-based interventions. Yoga asana, as a form of mind–body intervention, integrates physical postures, breathing techniques, and relaxation practices that may influence metabolic and psychosocial pathways relevant to T2DM. This article aimed to synthesize evidence regarding the physiological mechanisms, clinical effectiveness, and healthcare implementation context of yoga asana in T2DM management, as well as to discuss the role of physicians in integrating this complementary therapy, including within health tourism settings. A narrative literature review was conducted using scientific databases, focusing on publications addressing yoga asana, mind–body interventions, T2DM, and clinical integration. The findings indicate that yoga asana is associated with improved glycemic control, including reductions in fasting blood glucose, postprandial glucose, and HbA1c, alongside modulation of stress-related physiological parameters and psychological well-being. Beyond clinical outcomes, yoga asana shows potential for community-based and health tourism contexts as part of chronic disease lifestyle management. Physicians play a central role in clinical assessment, patient education, coordination with complementary therapy providers, and ongoing monitoring to ensure safe, evidence-based integration. Although current evidence suggests consistent beneficial trends, methodological heterogeneity highlights the need for more standardized and mechanistic research.